2022
DOI: 10.1242/jeb.243847
|View full text |Cite
|
Sign up to set email alerts
|

Why do ants differ in acclimatory ability? Biophysical mechanisms behind cuticular hydrocarbon acclimation across species

Abstract: Maintaining water balance is vital for terrestrial organisms. Insects protect themselves against desiccation via cuticular hydrocarbons (CHCs). CHC layers are complex mixtures of solid and liquid hydrocarbons, with a surprisingly diverse composition across species. This variation may translate to differential phase behaviour, and hence varying waterproofing capacity. This is especially relevant when temperatures change, which requires acclimatory CHC changes to maintain waterproofing. Nevertheless, the physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Here we do so too. A response in desiccation resistance to temperature as a cue (and specifically temperature acclimation) alone has been demonstrated in hemiedaphic and other Collembola ( Chown et al., 2007 ; Leinaas et al., 2009 ; Phillips et al., 2020 ) and in insects ( Terblanche and Chown, 2006 ; Fischer and Kirste, 2018 ; Baumgart et al., 2022 ). Using temperature as a cue to elicit a response to dry conditions not only has these empirical precedents, but also has a firm basis in theory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we do so too. A response in desiccation resistance to temperature as a cue (and specifically temperature acclimation) alone has been demonstrated in hemiedaphic and other Collembola ( Chown et al., 2007 ; Leinaas et al., 2009 ; Phillips et al., 2020 ) and in insects ( Terblanche and Chown, 2006 ; Fischer and Kirste, 2018 ; Baumgart et al., 2022 ). Using temperature as a cue to elicit a response to dry conditions not only has these empirical precedents, but also has a firm basis in theory.…”
Section: Introductionmentioning
confidence: 99%
“…Such a system appears to be conserved across invertebrates ( Russell et al., 2014 ; Enjin, 2017 ). Moreover, at high temperatures more cuticular hydrocarbons (CHCs) melt and those that are liquid show a viscosity decline ( Baumgart et al., 2022 ). Therefore, a theoretical expectation exists and some empirical data support the idea that temperature change alone should elicit a desiccation resistance response.…”
Section: Introductionmentioning
confidence: 99%
“…Second and more importantly, previous studies showed that acclimatory CHC changes are linked to drought resistance (Menzel et al, 2018). Also, for the ants studied here, warm acclimation significantly increased drought survival in both species compared to cold acclimation, with ants from the fluctuating treatment in between (Baumgart et al, in press). However, waterproofing not only requires solid or highly viscous compounds like n‐ alkanes and monomethyl alkanes.…”
Section: Discussionmentioning
confidence: 72%
“…Beside the lower effect sizes of acclimation in the PERMANOVA analyses, per cent changes between 20°C and 28°C treatments were much higher in L. platythorax than in L. niger . The lower acclimatory changes also affected fitness: the acclimatory increase in drought survival was substantially lower in L. niger than in L. platythorax (Baumgart et al, in press).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation